Non-Invasive Total Hemoglobin Measurement by Forehead Oximetry. - Priya M, Swadhi; Vidhya Lakshmi S, Sri; Mohammed A, Ashif; T. Jayanthi, Dr (International Journal of Engineering and Technology, 2018)
More than half a percentage of women across the world of reproductive age suffer from anemia. Low level of hemoglobin and partial pressure of oxygen plays a vital role in monitoring the level of anemia. The parameters of Spo2, total hemoglobinbin count,and heart rate have to be monitored when required to avoid various kinds of health complications. Finger oximetry and a blood test is the ideal and traditional method for monitoring Spo2 and measuring total hemoglobin count. If a patient is experiencing the severe anemic condition, an accurate measure of the above mentioned physiological parameters is necessary which are not done by the Traditional methods. So, the hardware is designed to measure these parameters with utmost accuracy. Recent works in forehead oximetry convey that it gives more accurate value than finger oximetry avoiding noise and motion artifacts. This idea comes up with measuring the Spo2, total hemoglobin count and heart rate over the forehead region by the optical method of using four different wavelengths and a heart rate sensor interfaced with the ARDUINO UNO Board to process the output and display it in the LCD. Non-Invasive monitoring of Spo2, total hemoglobin count,and heart rate is essential to know the oxygen saturation level in the body at any instant of time compared to standard biochemical test.Â Â